High-flow nasal cannula oxygen therapy to treat acute respiratory failure in patients with acute exacerbation of idiopathic pulmonary fibrosis. (May 2019) - Vianello, Andrea; Arcaro, Giovanna; Molena, Beatrice; Turato, Cristian; Braccioni, Fausto; Paladini, Luciana; Vio, Stefania; Ferrarese, Silvia; Peditto, Piera; Gallan, Federico; Saetta, Marina
Background: Some patients with idiopathic pulmonary fibrosis (IPF) develop acute exacerbation (AE-IPF) leading to severe acute respiratory failure (ARF); despite conventional supportive therapy, the mortality rate remains extremely high. The aim of this study was to assess how a treatment algorithm incorporating high-flow nasal cannula (HFNC) oxygen therapy affects the short-term mortality of patients with AE-IPF who develop ARF. Method and design: A retrospective cohort analysis was conducted. Patients and interventions: The study consisted of 17 patients with AE-IPF admitted to a respiratory intensive care unit (RICU) for ARF managed using a treatment algorithm incorporating HFNC. The outcome measure was mortality rate during their stay in the RICU. Results: Implementation of the treatment algorithm led to a successful outcome in nine patients and to a negative one in eight patients (47.1%) who died within 39 days of being admitted to the RICU. The survival rate was 70.6% (±0.1 %) at 15 days, 52.9% (±0.1%) at 30 days, 35.3% (±0.1%) at 90 days, and 15.6% (±9.73 %) at 365 days. Overall, 4 out of 10 patients who did not respond to conventional oxygen therapy showed a satisfactory response to HFNC. Conclusions: Short-term mortality fell to below 50% when a treatment algorithm incorporating HFNC was implemented in a group of patients with AE-IPF admitted to a RICU for ARF. Patients not responding to conventional oxygen therapy seemed to benefit from HFNC. The reviews of this paper are available via the supplementary material section.